UNDERSTANDING STOCK PRICE DYNAMICS: THE ROLE OF BOPO, NPL, INSTITUSIONAL OWNERSHIP AND MACROECONOMIC FACTORS - Hidayah, Fitri Rahmatun; Istiqomah, Dyah Febriantina (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study analyzes the impact of financial indicators (BOPO and NPL), non-financial factors (institutional ownership), and macroeconomic variables (inflation and interest rates) on stock prices. Using a quantitative approach, the research employed panel data regression analysis on a sample of 47 banking companies, selected via purposive sampling from 2021 to 2023, resulting in 141 observations. Data from financial reports were analyzed with EViews 12 software, encompassing model selection tests, classical assumption tests, and hypothesis testing. The findings reveal that NPL, institutional ownership, and interest rates significantly influence stock prices, whereas BOPO and inflation do not show a significant effect. These results suggest that investors prioritize long-term growth indicators like profitability, business expansion, and innovation over short-term operational efficiency metrics such as BOPO. Additionally, the insignificant impact of inflation may be attributed to its relative stability during the observation period. This research offers investors and corporate management crucial insights in making well-informed investment and strategic decisions.